2009
DOI: 10.1177/1091581809337737
|View full text |Cite
|
Sign up to set email alerts
|

Subchronic Oral Toxicity of Salcaprozate Sodium (SNAC) in Sprague-Dawley and Wistar Rats

Abstract: Salcaprozate sodium (SNAC) (sodium 8-((2-hydroxybenzoyl) amino) octanoate, CAS RN 203787-91-1) is classified as an oral absorption promoter, and its potential therapeutic applications as a delivery agent for oral forms of heparin and insulin have been explored in a number of clinical investigations. However, limited information about its nonclinical safety is available in the published scientific literature. As part of a larger study exploring the safety of SNAC in combination with heparin, Sprague-Dawley (SD)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 7 publications
0
18
0
Order By: Relevance
“…This carrier had a no observed adverse effect level (NOAEL) of 1 g/kg/day in rats [368], well above the doses used in oral peptide formulations. SNAC was tested in a number of clinical studies especially with heparin in phase III (PROTECT), where an oral liquid dose of heparin-SNAC failed to meet its primary endpoint; moreover compliance in this trial was low due to the bitterness of SNAC in solution, which had previously been noted in proof of principle clinical testing [369].…”
Section: Whatever the Mode Of Action Snac Was Granted Gras Status Inmentioning
confidence: 87%
“…This carrier had a no observed adverse effect level (NOAEL) of 1 g/kg/day in rats [368], well above the doses used in oral peptide formulations. SNAC was tested in a number of clinical studies especially with heparin in phase III (PROTECT), where an oral liquid dose of heparin-SNAC failed to meet its primary endpoint; moreover compliance in this trial was low due to the bitterness of SNAC in solution, which had previously been noted in proof of principle clinical testing [369].…”
Section: Whatever the Mode Of Action Snac Was Granted Gras Status Inmentioning
confidence: 87%
“…Specialised drug delivery companies have selected such excipients where possible, while others have funded studies designed to achieve 'GRAS status' for their delivery agents [267]. This is important because in order to effectively control chronic diseases, the dosage form should be amenable to regular administration.…”
Section: Future Perspectivementioning
confidence: 99%
“…Riley et al, carried out a sub-chronic oral toxicity test of SNAC in rats and found a no observed adverse effect (NOAEL) level of 1 g/kg/day in rats, with a massive dose of 2 g/kg/day eventually causing significant mortality. 26 Gastrointestinal (GI) effects such as emesis and diarrhea were observed in studies involving monkeys at a huge dose of 1.8 g/kg/day. A number of clinical studies have been published involving SNAC and also the related enhancer, 5-CNAC.…”
Section: Snacmentioning
confidence: 99%